Third molar impaction prevalence and pattern: a panoramic radiography investigation - Andi Nurul Azizah Tenrilili; Barunawaty Yunus; Fadhlil Ulum Abdul Rahman (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: The most commonly encountered impacted tooth is the third molar, and potential problems include oral cysts and tumors as well as caries, periapical lesions, periodontal disease, TMJ disorders, and root resorption of adjacent teeth. The aim of this investigation was to determine the third molar impaction prevalence and pattern. Materials and Methods: 530 panoramic radiographs of patients who visited Hasanuddin University Dental Hospital from January to December 2020 were collected. Data were recorded based on third molars region, eruption level, angulation, and impaction class from radiographs that met the criteria on Excel sheets and analyzed using SPSS 26. Chi square test was performed to assess relationship between impaction patterns with age and gender. The level of significance was fixed at p<0.05. Results: 115 radiographs were included and analyzed (45.2% male and 54.8% female). Third molar impaction prevalence was higher in females, in the age group 21-30 years, with level A eruption and vertical angulation. Most #38 and #48 demonstrated class 2 impaction. Apart from angulation and impaction class on #38, there was no significant difference between impaction patterns by age and gender group (p>0.05). Conclusion: Third molar impaction was more common in women aged 21-30 years with a dominant impaction pattern at level A with vertical angulation. In the mandible, class 2 of the Pell and Gregory classification are known to be dominant in third molar impaction.